Mutilation and Transformation : Damnatio Memoriae and Roman Imperial Portraiture - Varner, Eric (Monumenta Graeca et Romana, 2004)
The condemnation of memory inexorably altered the visual landscape of imperial Rome. Representations of 'bad' emperors, such as Caligula, Nero, Domitian, Commodus, or Elagabalus were routinely reconfigured into likenesses of victorious successors or revered predecessors. Alternatively, portraits could be physically attacked and mutilated or even executed in effigy. From the late first century B.C. until the fourth century A.D., the recycling and destruction of images of emperors, empresses, and other members of the imperial family occurred on a vast scale and often marked periods of violent political transition. This volume catalogues and interprets the sculptural, glyptic, numismatic and epigraphic evidence for damnatio memoriae and ultimately reveals its praxis to be at the core of Roman cultural identity.